New Insights Into Hepatic Impairment (HI) Trials - Sebastian Haertter; Maximilian Lobmeyer; Brian C. Ferslew; Pallabi Mitra; Thomas Arnhold (Clinical and Translational Science)
ABSTRACT Hepatic impairment (HI) trials are traditionally part of the clinical pharmacology development to assess the need for dose adaptation in people with impaired metabolic capacity due to their diseased liver. This review aimed at looking into the data from dedicated HI studies, cluster these data into various categories and connect the effect by HI with reported pharmacokinetics (PK) properties in order to identify patterns that may allow waiver, extrapolations, or adapted HI study designs. Based on a ratio ≥ 2 or ≤ 0.5 in AUC or Cmax between hepatically impaired participants/healthy controls these were considered “positive” or “negative”. In case of more than one HI severity stratum per compound included in the HI trial, the comparison of the AUC ratios for mild, moderate, or severe HI were used to investigate the increase across HI categories. For the in total 436 hits, relevant PK information could be retrieved for 273 compounds of which 199 were categorized negative, 69 positive ups and 5 positive downs. Fourteen out of 69 compounds demonstrated a steep increase in the AUC ratios from mild to severe HI. Compounds demonstrating a steep increase typically had a high plasma protein binding of > 95%, high volume of distribution, lower absolute bioavailability, minor elimination via the kidneys, were predominantly metabolized by CYP3A4 or CYP2D6 and the majority of these compounds were substrates of OATP1B1. While for compounds with steep increase studies in all severity strata may be warranted they may also offer the potential to estimate the appropriate doses in an HI trial. On the other hand, for compounds with slow or no increase across HI severity strata, reduced HI trials may be justified, e.g. only testing PK in moderate HI.